Proceso atención de enfermería en recién nacido con dificultad respiratoria - Bajaña Flores, Julexy Jamileth (2021)
This Clinical Case aims to publicize the nursing care process in a Newborn with Respiratory Difficulty, who was admitted to the pediatric area of the Baba Basic Hospital, for presenting symptoms of nasal flutter, rapid and shallow breathing It presents due to the immaturity of the lungs incapable of secreting surfactant, pulmonary immaturity and neurological incapacity to effect gas exchange efficiently, presenting itself at birth. Its incidence is higher in male neonates.